GC- MS, FTIR, UV Analysis and in vitro Antioxidant Activity of a Nigeria Poly Herbal Mixture: Pax Herbal Bitters - Elufioye, Taiwo Olayemi; O. Mada, Olubunmi (Free Radicals and Antioxidants)
Objective: The use of herbal products by the majority is primarily based on the belief that herbal drugs are safe, without any side effects, accessible and available at minimal cost. However, there is need for quality assurance of the botanicals in these products in order to meet the demands of product quality and efficacy. In this study, we aimed at identifying the chemical compositions of Pax herbal bitters towards a better understanding of its pharmacological claims. Methods: Pax herbal bitters purchased from licensed pharmacies in Nigeria was extracted separately with n-Hexane, Dichloromethane (DCM) and methanol. DPPH radical scavenging activity, total phenolic and total flavonoid content analysis of the various extracts were carried out. Chemical analysis of the extracts was also done using GC-MS, FTIR and UV. Results: The DPPH radical scavenging antioxidant activity showed highest activity in the DCM extract with an IC50 of 0.0167 while the total phenolic and total flavonoid content expressed as galic acid equivalents were found to be 20.00±0.23 and 2.55±0.01 for the methanol extract respectively and 5.39+ 0.01 and 2.54+ 0.14 for the DCM extract. The GC-MS, FTIR, and UV-VIS results showed that the herbal preparation contained compounds which may offer great pharmacological values. Some of the identified compounds include Isoborneol (0.61%, antioxidant, neuroprotective), Terpinen-4-ol (4.54%, anti-inflammatory, anti-fungi), 2, 4-Ditertbutylphenol (4.61% antioxidant, antifungi), Caryophyllene (9.33%, anti-inflammatory, anticancer), Isospathulenol (2.14%, immune-inhibitory), shogaol (15.16%, anti-cough, memory enhancer) and p-Heptylacetophenone (9.435%, anti-allergic). Conclusion: This study provides chemical basis for some of the claimed pharmacological actions of Pax herbal bitters.
Keywords: GC-MS; FTIR; UV-VIS Spectroscopy; Paxherbal Bitters; Pharmacological activity; Metabolites